Antibacterial Activity of Petung Bamboo Dendrocalamus Asper Leaf Extract Against Pathogenic Escherichia coli and Their Chemical Identification - Mulyono, Noryawati (International Journal of Pharmaceutical & Biological Archive, 2012)
Antibacterial Activity of Petung Bamboo Dendrocalamus Asper Leaf Extract Against Pathogenic Escherichia coli and Their Chemical Identification